Predicting hemodynamic indices in coronary artery aneurysms using response surface method: An application in Kawasaki disease. (September 2022) - Asadbeygi, Alireza; Lee, Simon; Kovalchin, John; Hatoum, Hoda
Highlights: Coronary artery aneurysms cause hemodynamics relevant to thrombosis & atherosclerosis. Kawasaki Disease aneurysms are used as example applications. The aneurysm shape indices effects on local hemodynamics are investigated. Response surface method is used for this investigation. Length and diameter of aneurysms are the main impactful factors. Abstract: Background and objectives: Coronary artery aneurysms (CAA), such as those in Kawasaki Disease (KD), induce hemodynamic alterations associated with thrombosis and atherosclerosis. Current clinical routines assess the risk level of the CAA cases based on the Z-Score, which considers the body surface area (BSA) and the CAA's diameter. A full geometric characterization and impact on hemodynamic metrics and their correlation with thrombotic risks have not been systematically investigated. The goal of this study was to investigate the effect of CAA shape indices on local hemodynamics using the response surface method (RSM) through considering KD applications. Methods: Transient computational fluid dynamics (CFD) simulations have been performed on idealized CAA geometries defined by geometrical ratios combining neck diameter, CAA diameter and CAA length. The results were used to develop full quadratic regression models of the indices using the response surface method (RSM). Validation using patient-specific KD models was performed. Results: The results indicated that the aneurysm diameter is the main determining factor in the thrombotic risk of CAA patients, which is consistent with clinical guidelines. Furthermore, it was observed that in most CAA cases having the same diameter, the one with the shorter length experiences higher RRT values, indicating flow stagnation and circulation. Conclusions: The developed regression models can be used to ultimately assess the thrombotic risk of CAA cases from the hemodynamic perspective. The applicability of these models was tested on 2 KD patient specific models, with close values achieved between the models and the patient-specific results.